Peer-review of study guide “Sheep pox and goat pox”. А. V. Kononov, O. P. Byadovskaya, K. A. Shalina, A. V. Sprygin, V. I. Diev . Vladimir: FGBI “ARRIAH”, 2021. 46 p.: fig. ISBN 978-5-900026-78-7 - T. I. Glotova (Ветеринария сегодня)
.